An overview on data aggregation in IOT For wireless sensor network - et. al., MOHAMMED SIRAJUDHEEN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
in recent days, there is a increasing attention in employing wireless sensor network (WSN) technologies in different scenarios of Internet of things (IoT). On considering the massive smart objects growth with their application, there is a demand to analyze and collect their product data are appropriate of the major challenge. Data aggregation is one of the prominent approaches in the removal of data redundancy and energy efficiency improvement; in addition it enhances the Wireless Sensor Networks lifespan. As well, the competent protocol on data aggregation might decrease network traffic. As a detailed intention takes place in a detailed region, it may be recognized through too much sensor. Considering the main aspects and challenges of data aggregation in WSN, an assessment on various kinds of data aggregation approach and protocol were presented in this approach. The eventual intention of this analysis is to create the basic details to expand novel higher designs depending on the techniques of data integration and clustering which have been presented so far. In this manuscript, various approaches has been described for the reduction of data redundancy and specifically in the aggregation of data.